2019
DOI: 10.1007/s42452-019-1712-9
|View full text |Cite
|
Sign up to set email alerts
|

MHD convection in a partially driven cavity with corner heating

Abstract: The paper presents a pertinent modification to the wall-moving thermal systems (classically represented by lid-driven cavity) by introducing a partial motion of the boundary walls. The effect of partial wall motion is investigated under magnetohydrodynamic (MHD) mixed convection in the cavity filled with porous medium. The corner heating arrangement is chosen for this investigation. The heater is placed at the right-bottom corner of the cavity, whereas the halves of the adjacent sides (which are moving) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Various types of complex problems (considering nanofluid/hybrid nanofluid, porous substances, magnetic fields, etc.) undergoing natural and mixed convection have been solved by the same code and several validations have been reported in our earlier works (Biswas et al, 2017;Mondal et al, 2019). However, using the reputed works (Sheremet and Pop, 2014;Nguyen et al, 2015), two new validation studies are conducted here to ensure the numerical accuracy of the present work.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…Various types of complex problems (considering nanofluid/hybrid nanofluid, porous substances, magnetic fields, etc.) undergoing natural and mixed convection have been solved by the same code and several validations have been reported in our earlier works (Biswas et al, 2017;Mondal et al, 2019). However, using the reputed works (Sheremet and Pop, 2014;Nguyen et al, 2015), two new validation studies are conducted here to ensure the numerical accuracy of the present work.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…For solving the pressure correction, velocity, and temperature equations, the under-relaxation factors are taken as 1.0, 0.4, and 0.9, respectively. The code has been validated repeatedly and extensively in the context of earlier works [4,[37][38][39]. Biswas et al [4] have reported the code validation under mixed convective heat transfer through porous media packed in a lid-driven cavity.…”
Section: Code Validationmentioning
confidence: 99%
“…The converged solutions are taken for the post-processing when the residuals and mass-defect fall below 10 À8 and 10 À10 , respectively. Earlier, this code with the appropriate validations (Biswas et al, 2015a;Biswas et al, 2015b;Biswas et al, 2016;Biswas et al, 2017;Biswas and Manna, 2018;Mondal et al, 2019) was used for simulating various flow situations undergoing natural or mixed convection. The capability of this code is continually enhanced to address newer flow physics.…”
Section: Numerical Aspectsmentioning
confidence: 99%